2004
DOI: 10.1002/ajh.20011
|View full text |Cite
|
Sign up to set email alerts
|

Rheological determinants in patients with Gaucher disease and internal inflammation

Abstract: The purpose of this study was to determine whether the inflammatory response in patients with Gaucher disease (GD) is accompanied by enhanced adhesiveness/aggregation of both red and white blood cells. Sixty patients with GD and matched controls were included. The degree of erythrocyte and leukocyte adhesiveness/aggregation was determined by using a simple slide test and image analysis. Patients with GD had significantly elevated concentrations of fibrinogen (328 vs. 262 mg/dl, P < 0.0001) and accelerated eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…Likewise, the normalization of the dot-plot profile of the two patients subsequently treated with ERT was associated with a normalization of RBC shape observed by SEM. The analysis of RBCs from another Gaucher patient who had (3,12) sometimes in the form of helmet cells (15). Dacryocytes or teardrop cells (8), echinocytes (2), and knizocytes (9,13) were found in most samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, the normalization of the dot-plot profile of the two patients subsequently treated with ERT was associated with a normalization of RBC shape observed by SEM. The analysis of RBCs from another Gaucher patient who had (3,12) sometimes in the form of helmet cells (15). Dacryocytes or teardrop cells (8), echinocytes (2), and knizocytes (9,13) were found in most samples.…”
Section: Discussionmentioning
confidence: 99%
“…Our results using SEM are in line with the latter finding, as we observed RBC aggregates in several untreated patients. Increased blood viscosity in GD may be related to a low-grade inflammatory state slowing down microcirculation flow and limiting oxygen supply to surrounding tissues (15,43). Inflammatory markers may not, however, fully account for the enhanced aggregation of Gaucher RBCs (16,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 However, RBC properties from GD patients have been investigated in a limited number of studies. [15][16][17][18] Among those is a hemorheologic study, which suggested a role for RBCs in the pathophysiology of GD. 16 This study prompted us to further investigate the properties of GD RBCs using multiple techniques, in particular flow adhesion assays.…”
Section: Introductionmentioning
confidence: 99%